Heat Transfer Characteristic on Wing Pairs Vortex Generator using 3D Simulation of Computational Fluid Dynamic - Petrus Setyo Prabowo; Stefan Mardikus; Ewaldus Credo (International Journal of Applied Sciences and Smart Technologies, 2021)
Vortex generators are addition surface that can increase heat transfer area and change the fluid flow characteristics of the working fluid to increase heat transfer coefficient. The use of vortex generators produces longitudinal vortices that can increase the heat transfer performance because of the low pressure behind vortex generators. This investigation used delta winglet vortex generator that was combined with rectangular vortex generator to Reynold numbers ranging 6,000 to 10,000. The parameters of Nusselt number, friction factor, velocity vector and temperature distribution will be evaluated.